Didactic Strategies for Autonomous Learning and their Impact on the Health of Students from a University in Lambayeque - Gioconda del Socorro Sotomayor Nunura; Doris Díaz de Angulo; Nelly Dioses Lescano; Humberto Iván Morales Huamán; Roberth Manuel Rivas Manay; José Alberto Silva Siesquén; Antenor Vásquez Muñoz (Revista Finlay, 2024)
Foundation: teaching strategies to promote autonomous learning are cognitive and affective strategies that facilitate: learning to learn, learning to do and learning cooperatively, to establish relationships with peers and achieve health well-being. Objective: determine the level of implementation of teaching strategies to achieve autonomous learning and its impact on the health of students at a private university in Lambayeque. Methods: a research was carried out with a quantitative approach, descriptive, cross-sectional and quasi-experimental design (before-after study). The sample was obtained through non-probabilistic convenience sampling with 390 students according to the inclusion criterion. Two variables were evaluated in their corresponding dimensions. For the statistical analysis, the IBM SPSS Statistics V.25 program was used. Results: for the variable, Teaching strategies, both in the pre-test and in the post-test, the majority rated it as: it always has an impact on mental health. Regarding the variable, Autonomous Learning, there was an increase in the rating for the option always, of 2.4 %, while in: sometimes, there was a decrease of 1.7 % and in: never, of 1.8 %, which showed the impact on the health of the students. Conclusions: teaching strategies were used to promote autonomous learning that allowed students to: select, organize, process and elaborate information; likewise, to develop motivation and self-regulation for awareness and control of their learning and improve mental health, by reducing stress levels.